Global burden and temporal trend of thyroid cancer associated with high BMI from 1990 to 2021 - Dan Pan; Ying-Xiu Diao; Yu-Xiang Pan; Zi-Hang Ai; Qing-Yang Liu; Zan-Bin Li (PLoS ONE, 2026)
The global incidence of thyroid cancer (TC) has risen markedly, ranking as the tenth most common malignancy in 2020. Simultaneously, obesity now affects over one billion individuals worldwide, with its prevalence more than doubling since 1990. Emerging evidence suggests a significant association between high body mass index (BMI) and elevated TC risk, potentially mediated by mechanisms such as chronic inflammation and insulin resistance. This study aims to evaluate the global burden of thyroid cancer attributable to high BMI (TC-HBMI) from 1990 to 2021, examine temporal trends, and project future burden through 2036. We utilized data from the Global Burden of Disease Study 2021 to assess deaths, disability-adjusted life years (DALYs), and age-standardized rates (ASRs). Temporal trends were examined using estimated annual percentage change (EAPC), joinpoint regression, and decomposition analysis. Inequality and future burden assessments were conducted through slope and concentration indices, frontier analysis, and Bayesian age-period-cohort modeling.